All Days 2010
DOI: 10.2118/137634-ms
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Investigation of Novel Oil Recovery Method for Carbonate Reservoirs

Abstract: The impact of brine salinity and ion composition on oil recovery has been an area of research in recent years. Evidence from laboratory studies supported by some field tests targeting mainly sandstones, has distinctly shown that injecting low salinity water has a significant impact on oil recovery. Although, the potential for carbonates has not been thoroughly investigated, some reported studies have excluded carbonates from this effect. The main objective of this paper is to investigate the potential of incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
167
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(187 citation statements)
references
References 33 publications
20
167
0
Order By: Relevance
“…5. It must be emphasized that the mechanism for improved oil recovery by removing NaCl from SW is different from the low salinity (LS) EOR effect observed by Yousef et al (2010) by diluting SW. For observing LS EOR effects in limestone, the formation must contain dissolvable anhydrite, CaSO 4 (s) . In that case, the catalyst, SO 4 2− , for the wettability alteration process is stored as a mineral in the formation, and when the LS fluid with low content of NaCl is flooded into the formation, the LS brine will be enriched in Ca 2 þ and SO 4 2− due to dissolution of anhydrite.…”
Section: Oilmentioning
confidence: 95%
“…5. It must be emphasized that the mechanism for improved oil recovery by removing NaCl from SW is different from the low salinity (LS) EOR effect observed by Yousef et al (2010) by diluting SW. For observing LS EOR effects in limestone, the formation must contain dissolvable anhydrite, CaSO 4 (s) . In that case, the catalyst, SO 4 2− , for the wettability alteration process is stored as a mineral in the formation, and when the LS fluid with low content of NaCl is flooded into the formation, the LS brine will be enriched in Ca 2 þ and SO 4 2− due to dissolution of anhydrite.…”
Section: Oilmentioning
confidence: 95%
“…Flooding with d 10 GSW improved the oil recovery by 3% of OOIP after flooding first with GSW. Yousef et al 10 observed the greatest kick in oil recovery when using 20 times diluted seawater.…”
Section: Energy and Fuelsmentioning
confidence: 99%
“…Recently, Yousef et al 10 showed that improved oil recovery was achieved when successively flooding composite reservoir carbonate cores with 2, 10, and 20 times diluted seawater. The oil recovery in each step increased by an additional 7, 9, and 1.5% of OOIP, respectively, after first flooding the core with ordinary seawater.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These new waterflooding strategies are economical and environment-friendly, and thus have attracted increasing interests from oil industry. The change of flooding efficiency by modifiedbrine is usually attributed to the dependence of wettability on brine ionic composition, 2,3,[12][13][14][15] which is denoted as ion-tuned wettability in this paper.…”
Section: Introductionmentioning
confidence: 99%